(untitled) - PRADANA AQUATAMA, RIO (Language Horizon: Journal of Language Studies, 2016)
Abstrak Tujuandaripenelitianiniuntukmengidentifikasidanmenganalisisjenistindakanilokusidari Chris Gardner sebagaikarakterutamadalam film yang berjudulPursuit of Happyness. Film iniberdasarkankisahnyatadari Chris Gardner yang memilikimimpibesaruntukdirinyadankeluarganya. Chris memilikikesempatanuntukmenjadipialangsaham, tetapiiaharusberada di anggotamagangpertama yang berartiiatidakmenerimagaji. Chris memutuskanuntukmelakukannyatapiketikaistrinyameninggalkannyadandiadiusir, diaharusmengurusanaknyasendiri. Jadimerekakadang-kadanghidup di jalandanberjuanguntukmelewatinya. Dan Chris bertekaduntukmelaluinya.Penelitianinimenggunakankeduametodekualitatifdankuantitatifuntukmelakukananalisisdalamrangkauntukmengeksposmasalahpenelitian; 1) jenistindaktuturilokusi yang munculpadapercakapan Chris, dan (2) alasantinndaktuturilokusi yang dominanmunculdaripercakapan Chris. Data termasukucapan-ucapandaripercakapandengantokohutamaberisitindakanilokusidalam film. Teori yang diterapkanuntukpenelitianiniadalahjenistindakanilokusioleh George Yule. Data telahdiklasifikasikankedalamlimaklasifikasi; representatif, direktif, komisif, ekspresifdandeklaratifdaritindaktuturilokusidandianalisissemua.Hasilpenelitianmenunjukkanbahwaada 488 ucapan yang berisitindakanilokusi. Yang ditemukan 204 ucapanatau 41,8% dari total data untukrepresentatifdengantindakan yang dilakukanseperti: menegaskan, menginformasikan, melarang, mengklaim, danbersikeras. Kemudiandiikutiolehdirektifdengan 176 ucapanatau 36,1% data dengantindakan yang dilakukanseperti: meminta, memerintah, meminta, pemesanan, memohon, danmenasihati. Ekspresifdigunakan di 72 ujaranatausekitar 14,7% dengantindakan yang dilakukanseperti: berterimakasih, memintamaaf, ucapan, mengejek, danmemuji. Sementaraitukomisfdigunakan di 34 ujaranatau 7% dengantindakan yang dilakukanseperti: menjanjikan, menawarkan, memprotes, mengancam, menerima, menolak, danmeyakinkan. Yang terakhiradalahdeclaratifdenganhanya 2 ucapanditemukanatauhanya 0,4% dari total data denganhanyamenemukan 1 tindakanyaitumenerimapekerjaan. Kata Kunci:tindaktuturilokusi, representatif, direktif, expresifs, komisif, deklaratif Abstract The purpose of this study to identify and analyze the types of illocutionary acts from Chris Gardner as the main Character in the movie entitled Pursuit of Happyness. This movie based on the true story from Chris Gardner who had big dream for him and his family. Chris had an opportunity to become stockbroker but he had to be in the internship member first which means he had no salary. Chris decided to do it but when his wife left and he was evicted, he had to take care of his son on his own. So they sometimes lived on the street and struggled to get by. But Chris was determined to make it.This study uses both qualitative and quantitative methods to do the analysis in order to expose the research problems which are; 1) the types of illocutionary acts that occur on Chris dialogues, (2) the function of illocutionary acts, and (2) the reason of dominant illocutionary acts that occur from Chris dialogue. The data included utterances from the conversation by main character contain illocutionary acts in the movie. The theory that were applied for this study was the types of illocutionary acts by George Yule. The data had been classified into five classification; representative, directive, commissive, expressive and declarative illocutionary acts and analyzed them.The result of the study showed that there are 488 utterances containing the illocutionary acts. That found 204 utterances or 41.8% from the total data for representative with the performed actions such as: asserting, informing, prohibiting, claiming, and insisting. Then followed by directive with 176 utterances or 36.1% data with performed actions such as: asking, commanding, requesting, ordering, pleading, and advising. Expressives used in 72 utterances or about 14.7% with the performed action such as: thanking, apologizing, greeting, mocking, and praising. Meanwhile commissives used in 34 utterances or 7% with performed actions such as: promising, offering, protesting, threatening, accepting, refusing, and assuring. The last is declaratives with only 2 utterances found or only 0.4%. Keywords:illocutionary acts, representatives, directives, expressives, commissives, declaratives